Automatically generating refactorings to support API evolution. - Perkins, Jeff H. (Software engineering notes.)
When library APIs change, client code should change in response, in order to avoid erroneous behavior, compilation failures, or warnings. Previous research has introduced techniques for generating such client refactorings. This paper improves on the previous work by proposing a novel, lightweight technique that takes advantage of information that programmers can insert in the code rather than forcing them to use a different tool to re-express it. The key idea is to replace calls to deprecated methods by their bodies, where those bodies consist of the appropriate replacement code. This approach has several benefits. It requires no change in library development practice, since programmers already adjust method bodies and/or write example code, and there are no new tools or languages to learn. It does not require distribution of new artifacts, and a tool to apply it can be lightweight. We evaluated the applicability of our approach on a number of libraries and found it to to be applicable in more than 75% of the cases.